Change is permanent: thoughts on the fading of cochineal-based watercolor pigments - Barbara H. Berrie; Yoonjoo Strumfels (Heritage Science, 2017)
Abstract Background Color change in artworks has been commented on for centuries. Fading of watercolor pigments is a notable alteration. Pigments based on carminic acid are among those particularly prone to color loss, but the mechanism and factors are not well understood. Results We painted out three pigments prepared from the aqueous extract of carminic acid (CA) from Dactylopius coccus: the uncomplexed, and aluminium- and tin-complexed lakes. These were applied in a 2% gum Arabic solution to papers that were acidic, neutral or alkaline pH and exposed to accelerated light aging in a weatherometer. The comparative rate of fading was dependent on the complexation and on the pH of the substrate. On alkaline paper, the Al complex was least light stable, on neutral paper the three colorants responded similarly, and on acidic paper the tin complex was the least light stable. This is discussed in light of the published information on reactions and mechanism of color loss of CA. Graphical abstract Cochineal-based pigments fade on exposure to light. In watercolor paints, the rate depends not only on the complexation of the ligand but also the pH of the paper substrate